La responsabilidad social de las organizaciones: ¿Factor de ventaja competitiva? Las acciones sociales de las organizaciones en relación con el tejido social (2019)
Approaching organizations from a systemic point of view allows us to see them as a group of interactive and interdependent parts of a larger system called society. This perspective lets us understand that each organization simultaneously affects and is affected by its environment, and this reciprocal relationship —of benefit or damage— largely determines its survival. This paper intends to explain, in a certain way, what is known today as social responsibility, although this concept has antecedents that go back to the end of the Nineteenth century and diverse manifestations throughout the Twentieth century. More recently, the negative effects of globalization, among other reasons, have forced the emergence of norms, behavioral codes and guides oriented to counteract those negative effects, seeking better working and social conditions. Each organization has an ethic, moral, and social imperative towards this responsibility, because that is how the organizations help to invigorate and/or recover social fabric, and to construct social capital. Every organization should assume social responsibility not only within, with its own employees, but also with its different stakeholders.